COMPREHENSIVE ANALYSIS ON THE EVALUATION OF FOCAL BREAST LESIONS USING ULTRASOUND ELASTOGRAPHY - 1Ibrahim Hudaid Almutairi, 2Waleed Saud S Aldughayyim, 3Siraj Gharee Eid Alqahtani, 4Faisal Rafe Almutairi, 5Majed Dakhilallah Almutairi, 6Faisal Miqad Alharbi, 7Khuloud Alhamaidi Almutairi, Almutairi, 8Bandar Awad M, (Chelonian Research Foundation, 2022)
Ultrasound elastography has developed as a promising strategy for surveying neighborhood breast lesions. It gives a better understanding of tissue firmness and can offer assistance in distinguishing between a generous and threatening illness. This article points to a comprehensive evaluation of the current state of ultrasound elastography in assessing breast lesions. A comprehensive writing audit examines the adequacy of different strategies, such as lesions elastography and shear wave elastography, within the breast cancer conclusion. The Think About section, moreover, gives charts outlining key focuses and decision-making forms, results, and discoveries from later ponders. Furthermore, the dialog examines the points of interest and confinements of ultrasound elastography, its potential impact on clinical practice, and future headings. The result uncovers critical discoveries and gives proposals for optimizing the use of ultrasound elastography in the assessment of breast lesions. Keywords: Breast lesions, ultrasound elastography, strain elastography, shear wave elastography, diagnosis, tissue stiffness.